Production, decomposition of residues and yield of maize and soybeans grown on cover crops (Revista Ciência Agronômica, 2015)
The residues of cover plants and crops left on the soil surface can influence decomposition, nutrient cyclingand follow crop yield. The objective was to evaluate the production of dry biomass (BD), of residues decompositionrate and yield of maize and soybean grown on different soil covers. The experimental design was a randomized blockscheme banded, with four covers: Brachiaria, sun hemp, pearl millet and fallow period in autumn/winter, with maizeand soybean crop in the spring/summer. We evaluated BD, decomposition through bags of decomposition and yield ofmaize and soybeans. Pearl millet and sunhemp were the covers which produced more of BD in the fall/winter period.the rate of decomposition of plant residues in maize and soybeans is slow in the dry period and accelerated in the rainyperiod; maize yield was higher when grown on sunhemp and brachiaria in the years evaluated, while for soybeans therewere no differences on any measured coverage; maize and soybeans have grain yields higher than the regional averagewhen grown on different soil covers.